Early antiviral and supervisory dexamethasone treatment improve clinical outcomes of nonsevere COVID-19 patients. Issue 45 (11th November 2022) - Sitasuwan, Tullaya; Phisalprapa, Pochamana; Srivanichakorn, Weerachai; Washirasaksiri, Chaiwat; Auesomwang, Chonticha; Tinmanee, Rungsima; Sayabovorn, Naruemit; Chayakulkeeree, Methee; Phoompoung, Pakpoom; Mayurasakorn, Korapat; Sookrung, Nitat; Tungtrongchitr, Anchalee; et al.
Abstract : This study aimed to evaluate the efficacy of early antiviral treatment in preventing clinical deterioration in asymptomatic or mildly symptomatic severe acute respiratory syndrome coronavirus 2 infected (COVID-19) patients in home isolation and to share our experiences with the ambulatory management of nonsevere COVID-19 patients. This retrospective study included mild COVID-19 adult patients confirmed by real-time reverse transcription-polymerase chain reaction. They received care via an ambulatory management strategy between July 2021 and November 2021. Demographic data, clinical progression, and outcomes were collected. Both descriptive and inferential statistics were performed to illustrate the cohort's characteristic and outcomes of the study. Univariable and multivariable logistic regression models were employed to investigate the associations between clinical factors and disease progression. A total of 1940 patients in the Siriraj home isolation system met the inclusion criteria. Their mean age was 42.1 ± 14.9 years, with 14.2% older than 60 years, 54.3% female, and 7.1% with a body weight ≥ 90 kg. Only 115 patients (5.9%) had deterioration of clinical symptoms. Two-thirds of these could be managed at home by dexamethasone treatment under physician supervision; however, 38 of the 115 patients (2.0% of the study cohort) needed hospitalization. Early favipiravir outpatient treatment (≤ 5 days from onset of symptoms) in nonsevere COVID-19 patients was significantly associated with a lower rate of symptom deterioration than late favipiravir treatment (50 [4.6%] vs 65 [7.5%] patients, respectively; P = .008; odds ratio 1.669; 95% confidence interval, 1.141–2.441). The unfavorable prognostic factors for symptom deterioration were advanced age, body weight ≥ 90 kg, unvaccinated status, higher reverse transcription-polymerase chain reaction cycle threshold, and late favipiravir treatment. The early delivery of essential treatment, including antiviral and supervisory dexamethasone, to ambulatory nonsevere COVID-19 patients yielded favorable outcomes during the COVID-19 pandemic in Thailand.